The structure of post-starburst galaxies at 0.5 < z < 2: evidence for two distinct quenching routes at different epochs - Maltby, David T.; Almaini, Omar; Wild, Vivienne; Hatch, Nina A.; Hartley, William G.; Simpson, Chris; Rowlands, Kate; Socolovsky, Miguel (Oxford University Press, 2018)
We present an analysis of the structure of post-starburst (PSB) galaxies in the redshift range 0.5 < z < 2, using a photometrically selected sample identified in the Ultra Deep Survey field. We examine the structure of ~80 of these transient galaxies using radial light μ(r) profiles obtained from CANDELS Hubble Space Telescope near-infrared/optical imaging, and compare to a large sample of ~2000 passive and star-forming galaxies. For each population, we determine their typical structural properties (effective radius re, Sérsic index n) and find significant differences in PSB structure at different epochs. At high redshift (z > 1), PSBs are typically massive (M* > 10^10 Msun), very compact and exhibit high Sérsic indices, with structures that differ significantly from their star-forming progenitors but are similar to massive passive galaxies. In contrast, at lower redshift (0.5 < z < 1), PSBs are generally of low mass (M* < 10^10 Msun) and exhibit compact but less concentrated profiles (i.e. lower Sérsic indices), with structures similar to low-mass passive discs. Furthermore, for both epochs, we find remarkably consistent PSB structure across the optical/near-infrared wavebands (which largely trace different stellar populations), suggesting that any preceding starburst and/or quenching in PSBs was not strongly centralized. Taken together, these results imply that PSBs at z > 1 have been recently quenched during a major disruptive event (e.g. merger or protogalactic collapse) that formed a compact remnant, while at z < 1 an alternative less disruptive process is primarily responsible. Our results suggest that high-z PSBs are an intrinsically different population to those at lower redshifts, and indicate different quenching routes are active at different epochs.